Improvement of Jangguik Rice Genotype Characters (Oryza sativa L. ) Through Gamma-ray Mutation Induction in the Nursery Phase - Wahyudi; Elfi Indrawanis; Gusti Marlina (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Rice is a widely cultivated and consumed food commodity. In Indonesia, the increasing population growth has led to a rise in both rice consumption and demand. The purpose of this study was to determine the effects of gamma-ray treatment on the properties of Jangguik rice, specifically regarding seed growth duration, seedling height, number of leaves, and seedling weight. The research was conducted in Koto Kari Village, located in the Kuantan Tengah District of Kuantan Senggigi Regency. The Deputy provided gamma irradiation services for Research and Innovation Infrastructure at the Yogyakarta Radiation Laboratory, situated on Jl. Babarsari, Depok, Sleman, Yogyakarta. The research was conducted over two months, from June to July 2024. This experiment employed an experimental method utilizing a Randomized Block Design with one factor. The study consisted of five treatments, each repeated three times, resulting in a total of 15 experimental plots. The treatments tested included doses of 0 Gy, 100 Gy, 200 Gy, 300 Gy, and 400 Gy. The study's results were analyzed statistically using an ANOVA table. If the calculated F-value exceeded the F-value from the table at the 5% significance level, further analysis was conducted using the Honestly Significant Difference (HSD) test at the same significance level. The results of the study indicate that gamma-ray irradiation treatment exerts a multifaceted impact on the growth of Jangguik rice seedlings. The following data were collected for analysis: the parameter of seed growth days (0 Gy treatment: 3.41 days after planting; 300 Gy treatment: 6.06 cm); the number of leaves (200 Gy: 5.46 pieces); and the weight of 100 Gy seedlings (0.146 grams).